HASIL BELAJAR BIOLOGI MENGGUNAKAN STRATEGI PEMBELAJARAN AKTIF INDEX CARD MATCH DITINJAU DARI MOTIVASI - Rahmawati, Aprillia Diah; Rosyidi, Alvi; Probosari, Riezky Maya (Pendidikan Biologi, 2011)
ABSTRACT ? The purposes of this research were to know: 1) the influence of index card match active learning strategy to the result of study biology; 2) the influence of student?s learning motivation to the result of study biology; 3) the interaction between learning strategy and learning motivation to the result of study biology: and 4) the influence of better learning strategy to the result of study biology. Background problems in this research are biology teachers, in general, are still not implementing the strategy of active learning in delivering learning, some teachers are oriented to the achievement of the cognitive. Lack of interaction between teacher and student, and also teachers do not involve students actively in each learning activity. Students? motivation  in learning Biology is low because some students take identical biological material by rote.  Index Card Match  is an appropriate strategy applied to high school students because these strategies involve students in active, containing elements of the game, and gives a nice effect that will facilitate and enhance motivation to learn more diligent and to obtain the optimal results of biological studies.  This research was quasi experiment research using  Randomized Control Only design.  Independent variables were  learning strategy and learning motivation, whereas student?s achievement of study biology was the dependent variable. The population of this research was all on X grade of SMA Negeri 5 Surakarta. The samples of this research were the students of class X-3  as the control group and students of class X-4 as the experimental group.  The sample of this research was established by cluster random sampling. The data about the result of study biology collected by use test and observation.  Learning motivation meansured by using questionnaires. The analisis of this research was anava two away in different cell and the advance test used Bunfferoni test. The conclusion of this research were: 1) Index card match active learning strategy had significant influence to the  result of study biology (cognitive, affective and pshycomotor domain) on X grade of SMA Negeri 5 Surakarta; 2) Learning motivation had significant influence to the result of study biology on X grade of SMA Negeri 5 Surakarta; 3) There wasn?t interaction between learning strategy and learning motivation to the result of study biology (cognitive, affective and pshycomotor domain) on X grade of SMA Negeri 5 Surakarta. Keywords : student?s biology achivement, index card match active learning strategy, and learning motivation